2020
DOI: 10.1158/2159-8290.cd-20-0516
|View full text |Cite
|
Sign up to set email alerts
|

Case Fatality Rate of Cancer Patients with COVID-19 in a New York Hospital System

Abstract: Cancer patients are presumed to be at increased risk from COVID-19 infection fatality due to underlying malignancy, treatment-related immunosuppression, or increased comorbidities. A total of 218 COVID-19 positive patients from March 18th-April 8th, 2020 with a malignant diagnosis were identified. A total of 61 (28%) cancer patients died from COVID-19 with a case fatality rate (CFR) of 37% (20/54) for hematologic malignancies and 25% (41/164) for solid malignancies. 6/11 (55%) lung cancer patients died from CO… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

72
893
18
46

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 742 publications
(1,029 citation statements)
references
References 13 publications
72
893
18
46
Order By: Relevance
“…A current report indicated the SARS-CoV-2 variant with Spike D614 to G614 increased the infectivity of the COVID-19. [19] However, the mortality of our study (6.7%) was much lower than that of general cancer patients (11.4-18.6%) [5,[8][9][10]. Besides, as to disease severity, 26.7% of breast cancer patients in our study had severe disease, which still lower than that of general cancer patients observed by H. Zhang (47.8%), Ma (54.1%), and Dai (34.3%) [7,8,20].…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…A current report indicated the SARS-CoV-2 variant with Spike D614 to G614 increased the infectivity of the COVID-19. [19] However, the mortality of our study (6.7%) was much lower than that of general cancer patients (11.4-18.6%) [5,[8][9][10]. Besides, as to disease severity, 26.7% of breast cancer patients in our study had severe disease, which still lower than that of general cancer patients observed by H. Zhang (47.8%), Ma (54.1%), and Dai (34.3%) [7,8,20].…”
Section: Discussioncontrasting
confidence: 54%
“…With the rapid progression of COVID-19 worldwide, it is inevitable that large numbers of cancer patients will be affected by this pandemic [5][6][7][8][9][10]. This leads to grave concerns about standard-of-care treatment regimens in COVID-19 era and the adoption of protective measures, such as postponing active cancer treatments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to their potentially immune-compromised status, the proper treatment of cancer patients is a real and serious problem being faced by oncologists, regardless of if the patient is experiencing a SARS-CoV-2 infection [16]. Data from four SARS-CoV-2 hot spots (the United States, Italy, Spain and China) has shown that cancer patients infected with the novel coronavirus have a signi cantly increased risk of admission to an intensive care unit (ICU) and/or requiring mechanical ventilation, as well as an increase in patient mortality [15,[17][18][19]. In a retrospective study, the fatality rate for cancer patients in China infected with COVID-19 was found to be approximately 28% [20], compared to the overall symptomatic fatality rate of 1.4% or the crude mortality rate of 4.5% in China [21].…”
Section: Cancer Patients and The Covid-19 Epidemicmentioning
confidence: 99%
“…It is now clear that among hospitalized patients with COVID-19, pneumonia, sepsis, and respiratory failure are frequent complications, with some patients predisposed to poor clinical outcomes 2,3 , while uncertainty regarding management of the complications arose in the course of this viral illness. 4 To reasonably improve the prognosis of COVID-19 patients with complications, effective risk strati cation and early intervention for patients are urgently needed.…”
Section: Introductionmentioning
confidence: 99%